Regulation of exosome secretion and functions by mTORC1 signalling and the microenvironment - Perera, M (2017)
Cancer cells require survival strategies to respond to microenviromental changes and out-compete their neighbours. They activate stress response mechanisms under extreme microenvironmental conditions, some of which are controlled by the amino acid-sensitive kinase complex, mechanistic Target of Rapamycin Complex 1 (mTORC1). Exosomes are secreted nanovesicles made inside intracellular endosomal compartments that mediate a specialised and complex form of intercellular signalling that can reprogramme target cells via the action of multiple active cargos. I investigated whether mTORC1 activity might modulate the type of exosome secreted in response to microenvironmental changes. Here I identify a new form of mTORC1-regulated exosome biogenesis and signalling involving recycling multivesicular endosomes (rMVEs), a previously unrecognised site for exosome biogenesis. Reduced activity of a specific form of glutamine-sensitive mTORC1 in HCT116 colorectal cancer cells results in an ‘exosome switch’ in which exosomes are preferentially released from these compartments instead of late endosomes. Importantly, RAB11a is found in association with at least a proportion of rMVEs that generate these alternative exosomes and is loaded on to some of their ILVs, providing a RAB signature of compartmental origin. I provide evidence that this exosome switch is conserved in other cancer cell types. My study also presents a proteomics analysis of extracellular vesicle (EV) preparations from normal and mTORC1-inhibited cells. I demonstrate that EV preparations isolated following exosome switching have enhanced pro-angiogenic properties and novel tumour growth-promoting activities. Activation of the receptor tyrosine kinase c-MET and its downstream mitogen-activated protein kinase (MAPK) ERK via phosphorylation is stimulated by these EVs, providing a potential explanation for their growth-promoting effects. Subsequent studies in the lab have demonstrated that several of these pro-tumorigenic activities are mediated by exosomes. I conclude that stress-induced mTORC1 inhibition allows tumour cells to initiate a novel exosome secretion pathway that potentially mediates a cancer cell survival plan that reverses microenvironmental change and supports tumour adaptation. In the future, blocking this response could improve patient outcome following treatment with mTORC1-inhibitory or anti-angiogenic drugs that have currently met with limited success in the clinic.